2021
DOI: 10.3389/fncel.2021.752771
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Trifluoperazine on Peripheral Proinflammatory Cytokine Expression and Hypothalamic Microglia Activation in Obese Mice Induced by Chronic Feeding With High-Fat-Diet

Abstract: Microglia and astrocytes are the glial cells of the central nervous system (CNS) to support neurodevelopment and neuronal function. Yet, their activation in association with CNS inflammation is involved in the initiation and progression of neurological disorders. Mild inflammation in the periphery and glial activation called as gliosis in the hypothalamic region, arcuate nucleus (ARC), are generally observed in obese individuals and animal models. Thus, reduction in peripheral and central inflammation is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moreover, trifluoperazine blocks postsynaptic D2Rs in midbrain limbic and cortical projections 39 . Reports have demonstrated that 2–3 mg/kg TFP‐2HCl affects the central nervous system in mice 40–42 . SCH772984 is a selective ERK1/2 inhibitor that binds to unphosphorylated and inactive ERK1/2 and effectively inhibits ERK1/2 phosphorylation 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, trifluoperazine blocks postsynaptic D2Rs in midbrain limbic and cortical projections 39 . Reports have demonstrated that 2–3 mg/kg TFP‐2HCl affects the central nervous system in mice 40–42 . SCH772984 is a selective ERK1/2 inhibitor that binds to unphosphorylated and inactive ERK1/2 and effectively inhibits ERK1/2 phosphorylation 43 .…”
Section: Discussionmentioning
confidence: 99%
“… 39 Reports have demonstrated that 2–3 mg/kg TFP‐2HCl affects the central nervous system in mice. 40 , 41 , 42 SCH772984 is a selective ERK1/2 inhibitor that binds to unphosphorylated and inactive ERK1/2 and effectively inhibits ERK1/2 phosphorylation. 43 Previous research has reported that the effective dose range of SCH772984 in mouse models is 10–20 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Trifluoperazine suppresses the release of cytokines and exerts anticancer effects [38]. Recently, trifluoperazine has been observed to reduce the levels of interleukin-1-beta and TNF-alpha, attenuating the production of proinflammatory mediators [39,40]. Huang et al, (2021) have described that trifluoperazine reduces hypothalamic inflammation in the acute stage by suppressing gliosis induced by saturated fatty acids and inhibiting the protein calmodulin, which binds to Ca+2 in edema brain processes [39,41].…”
Section: Trifluperidol Trifluoperazine Disulfiram and Haloperidol Wou...mentioning
confidence: 99%
“…Recently, trifluoperazine has been observed to reduce the levels of interleukin-1-beta and TNF-alpha, attenuating the production of proinflammatory mediators [39,40]. Huang et al, (2021) have described that trifluoperazine reduces hypothalamic inflammation in the acute stage by suppressing gliosis induced by saturated fatty acids and inhibiting the protein calmodulin, which binds to Ca+2 in edema brain processes [39,41]. Therefore, this drug modulates metabolic dysfunction, where it has been described that its administration has a positive effect on the homeostasis of the glucose pathway [39,42,43].…”
Section: Trifluperidol Trifluoperazine Disulfiram and Haloperidol Wou...mentioning
confidence: 99%
See 1 more Smart Citation